Evaluating mtDNA patterns of genetic isolation using a re-sampling procedure: A case study on Italian populations. (17th February 2017) - Anagnostou, Paolo; Capocasa, Marco; Dominici, Valentina; Montinaro, Francesco; Coia, Valentina; Destro-Bisol, Giovanni
Abstract: Background: A number of studies which have investigated isolation patterns in human populations rely on the analysis of intra- and inter-population genetic statistics of mtDNA polymorphisms. However, this approach makes it difficult to differentiate between the effects of long-term genetic isolation and the random fluctuations of statistics due to reduced sample size. Aim: To overcome the confounding effect of sample size when detecting signatures of genetic isolation. Subjects and methods: A re-sampling based procedure was employed to evaluate reduction in intra-population diversity, departure from surrounding genetic background and demographic stationarity in 34 Italian populations subject to isolation factors. Results: Signatures of genetic isolation were detected for all three statistics in seven populations: Pusteria valley, Sappada, Sauris, Timau settled in the eastern Italian Alps and Cappadocia, Filettino and Vallepietra settled in the Appenines. However, this study was unable to find signals for any of the statistics analysed in 19 populations. Finally, eight populations showing signals of isolation were found for one or two statistics. Conclusion: The analysis revealed that the use of population genetic statistics combined with re-sampling procedure can help detect signatures of genetic isolation in human populations, even using a single, although highly informative, locus like mtDNA.